Bedrock geochemistry influences vegetation growth by regulating the regolith water holding capacity - Jiang, Zihan; Liu, Hongyan; Wang, Hongya; Peng, Jian; Meersmans, Jeroen; Green, Sophie M.; Quine, Timothy; Wu, Xiuchen; Song, Zhaoliang (Nature Publishing Group, 2020)
Although low vegetation productivity has been observed in karst regions, whether and how bedrock geochemistry contributes to the low karstic vegetation productivity remain unclear. In this study, we address this knowledge gap by exploring the importance of bedrock geochemistry on vegetation productivity based on a critical zone investigation across a typical karst region in Southwest China. We show silicon and calcium concentrations in bedrock are strongly correlated with the regolith water loss rate (RWLR), while RWLR can predict vegetation productivity more effectively than previous models. Furthermore, the analysis based on 12 selected karst regions worldwide further suggest that lithological regulation has the potential to obscure and distort the influence of climate change. Our study implies that bedrock geochemistry could exert effects on vegetation growth in karst regions and highlights that the critical role of bedrock geochemistry for the karst region should not be ignored in the earth system model
Keywords: Biogeochemistry; Ecology